Rethinking Participation in Commons Governance: Political Representation and Participation. Issue 8 (3rd August 2021) - Fudge, Maree; Leith, Peat
Abstract: Participatory practices are prominent strategies for increasing the legitimacy and effectiveness of resource commons governance. Despite increases in participatory practices legitimacy of such governance is in decline. Remaining commons are sites of conflict echoing wider disillusionment in democratic governance across mature liberal democracies. Much participatory governance literature argues that more involvement of citizens in deliberation and decision-making is the solution, turning away from representative practices to strengthen direct participation in commons governance. In this paper we draw on seminal work in political representation theory to examine legitimacy and political agency in participatory governance practices. We develop a conceptual lens drawing on key elements of: Hannah Pitkin's The Concept of Representation; Michael Saward's Representative Claim; and, Vivan Schmidt's throughput model of legitimacy. The lens comprises three 'conditions' for analyzing how political agency of participants is constituted through institutional processes: authorization, dissent and exit, and accountability. We argue that this conceptual lens can serve the participatory turn in commons governance by enabling explicit consideration of the links between political participation and representation as foundations of democratic legitimacy.